Adomian decomposition method for optimal control problems of biomedical systems - İnç, Mustafa (My University, 2001)
The decomposition method can be used to solve a wide class of non-linear functional equations. This method uses a series solution with rapid convergence. Many biomedical models lead to differential systems where some of the parameters have to be identified from partial observation of the system's solution. In this work we propose new numerical methods based on Adomian's method for solving optimal control problems associated with biomedical systems.
Keywords: Mühendislik; Biyotıp; Matematik